A literature review of systemic to pulmonary collaterals in preterm infants to emphasise their existence and clinical importance. (2nd July 2018) - Goel, Dimple; Gupta, Pankaj; Cooper, Stephen; Klimek, Jan
Abstract: Aim: Cardiorespiratory physiology plays an important role in neonatal care with increasing utility of point‐of‐care ultrasound. This review is to bring to light the importance of systemic to pulmonary collaterals (SPCs) in the preterm population without congenital heart disease (CHD) and provide a useful diagnostic tool to the neonatologist performing a cardiac ultrasound. Methods: Medline, PubMed, EMBASE and the Internet were searched up to November 2017 for articles in English which included SPCs in preterm infants without CHD. This comprised title, abstract and full‐text screening of relevant data. Results: A total of 10 studies which included case reports, retrospective observational studies and one small prospective cohort study were identified and analysed in detail. The studies had varying focus such as variable incidence, clinical presentation, association with chronic lung disease, pathophysiology and clinical importance of SPCs. SPCs were overall thought to be prevalent, underdiagnosed and of clinical significance in preterm infants. Conclusion: Systemic to pulmonary collaterals are a potential left‐to‐right shunt in preterm infants and may contribute to worsening chronic lung disease (CLD) or heart failure. They should be carefully looked for when performing bedside cardiac ultrasound as the findings can mimic those seen in patent ductus arteriosus (PDA).